STUDIES ON COMPATIBILITY, FRUIT SET AND FRUIT QUALITY BY DIFFERENT POLLINATORS IN ANNA APPLE CULTIVAR - Mahmoud Maklad; Mai Anwar; نظمي عبد الغني; Nahla Awad (Arab Universities Journal of Agricultural Sciences, 2020)
The apple (Malus domestica) is a member of the Rosaceae family. It is older than the rose in cultivation and is often referred to as the prince of the rose family. Pollen grains of Dorsett Golden, E25 and Ein Shemer were used to investigate their compatibility and incompatibility with Anna cultivar under the Egyptian climatic conditions during two successive experimental seasons of 2016 and 2017. The fluorescence microscope was used to determine the degree of pollen tube growth in style tissue after specific pollination treatments. Degree of self and cross compatibility and or incompatibility were determined, initial, and final fruit set percentage were calculated. Pollination treatments revealed that, pollens of the four apple cultivars exhibited high rate of the viability after 24 hr. in T.T.C test. Growth of pollen tube of the tested cultivars exhibited different pattern of compatibility, the pollen tubes of Dorsett Golden and Ein Shemer cultivars showed different levels of cross-compatibility when fertilized in Anna style tissue. The pollen tube of E25 cultivar grew slowly with heavy deposition of calluses along to the tube where its growth stopped in the lower part of Anna style four days after pollination. Therefore, they need pollinizer cultivars as for good fruit set. On the other hand, Anna self-pollination seemed to be self-incompatible and recorded lowest initial of fruit set percentage in the first and second seasons. The combinations of Anna × Dorsett Golden exhibited maximum percentage of initial and final fruit set in the two seasons followed by Ein Shemer pollens in both seasons. Insignificant differences were noted in fruit weight and fruit volume among all crosses. The highest acidity was found in hybrid Anna × Dorsett Golden in except in the first season TSS values of these crosses were not high and ranged between 11.83 % and 12.83 %.